Reintegration Needs of Young Women following Genitourinary Fistula Surgery in Uganda - Emasu, Alice; Matovu, Alphonsus; Alia, Godfrey; Barageine, Justus Kafunjo (Int Urogynecol J, 2019)
Genitourinary fistulas (usually arising following prolonged obstructed labor) are particularly devastating for women in low-income counties. Surgical repair is often difficult and delayed. While much attention has been devoted to technical surgical issues, the challenges of returning to normal personal, family, and community life after surgical treatment have received less scrutiny from researchers. We surveyed young Ugandan women recovering from genitourinary fistula surgery to assess their social reintegration needs following surgery.